Ideas, Intentos y Fracasos en el Proceso Modernización Administrativa Entre Las Dos Administraciones de Ibáñez (1927-1958) - Arias-Yurisch, K (Universidad de Talca, 2012)
In the aftermath of the First World War, from 1925 onwards, the Chilean state was subject of important changes in its structures and functions. Coronel Carlos Ibáñez del Campo, who governs the nation between 1926 and 1931 directly or indirectly, led that process. Ibáñez embodied the demands and ideas of the middle sectors, which aspired to more participation in the affairs of the state. The attempts of reform resulted in a growth of the size of the public sector and the creation of autonomous of public agencies. Nevertheless, these changes were not part of an integral project of administrative modernization, but rather isolated initiatives, which lacked in mid and long term goals. This is understood a case of an unsuccessful modernization attempt, as it turn out evident in the 1950 s.